BSDES With Stochastic Lipschitz Condition - Christian Bender; Michael Kohlmann (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
We prove an existence and uniqueness theorem for backward stochastic differential equations driven by a Brownian motion, where the uniform Lipschitz continuity is replaced by a stochastic one.
urn:nbn:de:bsz:352-opus-4241
Keywords: 330; Analysis; Stochastischer Prozess; Theorie